Evidence of Sediment Sterility and Benthic Quality as Deleterious Consequences after the 2019 oil Spill in Northeastern Brazil (Global Journal of Science Frontier Research, 2022)
The worst environmental oil spill disaster ever recorded in any tropical coastal region globally happened in 2019; severely affecting one of Brazil most famous northeast tourist area South Pirangi Reef area in the state of Rio Grande do Norte (RN). The oil, a complex chemical mixture of hydrocarbon including heavy metals spilled on beaches, in estuaries, and reefs has spread between 50 cm and 1 m deep, occasionally sinking to the benthos. Death of oiled animals and Habitat destruction are acute and long-term consequences on ecological systems that rely on the now impacted environment for survival. Pirangi Reef which was subjected to the oil spill in October 2019, was previously studied in 2013 and 2014 with no spotting of oil patches in the 55 sediment or water samples at that time. After the oil spill, 25 new sites in the reef areas, sandy sediments and macroalgae substratum were sampled to compare temporal data after the disastrous event. Our findings show that more than 95% of the unconsolidated sediment samples, including some corals, had some evidence of oil in 2019 opposed to no evidence at all in 2013 and 2014. Data on benthic foraminiferal fauna show loss of 26 species including symbiotic species.
Keywords: environmental disaster; crude oil; foraminifera; coral reef; baren zone; river